1990
DOI: 10.1037/0022-0167.37.3.343
|View full text |Cite
|
Sign up to set email alerts
|

Anchoring errors in clinical judgments: Type I error, adjustment, or mitigation?

Abstract: The nature of anchoring errors in clinical judgments was clarified. Study 1 tested if gender mediates the occurrence of anchoring errors. Judgments from 103 undergraduate psychology students evidenced neither anchoring errors nor gender differences. Given the inability to replicate Friedlander and Stockman's (1983) study, two rival hypotheses were advanced: the adjustment hypothesis (practitioners adjust appropriately their clinical judgments after receiving new client information) and the adjustment mitigatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
28
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 30 publications
0
28
0
Order By: Relevance
“…This is not inconsistent with the premises of the thesis proposed by Asch (1946). It has been found that clinical anchoring in early-divulged information is indeed in evidence in clinical judgment but that it can be attenuated when sufficiently discrepant information is provided later (Ellis, Robbins, Schult, Ladany, & Baker, 1990;Strohmer et al, 1990). Clinical judgments about clients seem to be based on initial impressions rather than the exhaustive observation and hypothesis testing, which are characteristics of sound scientific inquiry.…”
mentioning
confidence: 59%
“…This is not inconsistent with the premises of the thesis proposed by Asch (1946). It has been found that clinical anchoring in early-divulged information is indeed in evidence in clinical judgment but that it can be attenuated when sufficiently discrepant information is provided later (Ellis, Robbins, Schult, Ladany, & Baker, 1990;Strohmer et al, 1990). Clinical judgments about clients seem to be based on initial impressions rather than the exhaustive observation and hypothesis testing, which are characteristics of sound scientific inquiry.…”
mentioning
confidence: 59%
“…Another possibility is that clinicians were indeed making the subsequent ratings on the nonessential criteria without being affected by (i.e., anchoring on) the essential information (cf. Ellis et al, 1990). …”
Section: Severity Of "Essential Diagnostic Information"mentioning
confidence: 93%
“…Given previous evidence that halo effects are typically assimilation effects, clear-cut DNVB was predicted to increase the severity of symptom ratings when compared to near-threshold DNVB. Directional predictions for either of the other two information manipulations (expectancy and anchoring) were not made given the lack of previous results in a consistent direction (e.g., Bieri et al, 1963;Ellis, Robbins, Schult, Ladany, & Banker, 1990;Lee et al, 1992;Markovsky, 1988;Plous, 1989).…”
Section: Studymentioning
confidence: 96%
“…The analog case methodology has been utilized in prior research (Ellis, Robbins, Schult, Ladany, & Baker, 1990;Hansen, Warner-Rogers, & Hecht, in press;Howe, Herzberger, & Tennen, 1988;Pain & Sharpley, 1989) and has been called for as a necessary approach to systematically examine clinical judgment (Lopez, 1989). The methodology is very useful for establishing experimental control, however it is unknown how results of this particular analog model would relate to judgments in actual practice.…”
Section: Discussionmentioning
confidence: 99%